2012
DOI: 10.24023/futurejournal/2175-5825/2012.v4i1.75
|View full text |Cite
|
Sign up to set email alerts
|

FONTES EXTERNAS DE TECNOLOGIA: O CASO DE UMA INDÚSTRIA DE CERÂMICA VERMELHA <br><strong>DOI:10.7444/fsrj.v4i1.75</strong>

Abstract: Competitiveness is one of the main issues in business nowadays. The entrepreneur's economic environment requires the ability to leverage the productive resources available. This paper aims to study the stage of identifying external sources of technological information in a red ceramic industry. Initially, we made a comprehensive review of the literature about strategy, management and sources of technology. In addition, we made a contextualization of the ceramic sector in Brazil. Then, we applied a case study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(4 reference statements)
0
0
0
Order By: Relevance
“…A recent survey showed that most of these producers are family-based enterprises with low or none technological profile; furthermore, both wood (primary heat source) and clays (primary raw material) are obtained mainly by extractive methods without environmental, economic or performance criteria. In spite of that, the state's production reached 2.7 billion pieces in 2014, with creation of about 12,000 direct jobs [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey showed that most of these producers are family-based enterprises with low or none technological profile; furthermore, both wood (primary heat source) and clays (primary raw material) are obtained mainly by extractive methods without environmental, economic or performance criteria. In spite of that, the state's production reached 2.7 billion pieces in 2014, with creation of about 12,000 direct jobs [4][5].…”
Section: Introductionmentioning
confidence: 99%